Study on the Productive and Reproductive Performances of Red Chittagong Cow at rural areas in Chittagong - Azizunnesa, M; Sutradhar, BC; Hasanuzzaman, M; Miazi, OF; Aktaruzzaman, M; Faruk, MO (University Journal of Zoology, Rajshahi University, 2010)
The result of the collected data revealed different reproductive performances of Red Chittagong Cow such as age at puberty 2.68±1.72 years, days required to first heat during post partum period 3.08±1.00 months, calving interval 14.00±1.19 months, service per conception 1.36±0.60 and gestation length 279.92±5.27 days. In this survey some data were recorded to observe the production performances of Red Chittagong Cows. Milk production per day and lactation length was 2.10±0.63 liter and 238.8±30.6 days, respectively. The maximum milk production per day was 4 liter per cow and the minimum production was 1 liter per day per cow. The cow produced 1.88±0.51 liter milk supplied with roughage only on the other hand 2.42±0.57 liter milk produced by the cow supplied some amount of concentrate along with roughage. The level of production difference between two groups were highly significant (p<0.0001). Key Words: Lactation; Puberty; Service per conception; RCC. DOI: 10.3329/ujzru.v28i0.5282 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 27-31